Factors influencing the in situ generation of hydrogen peroxide from the reduction of oxygen by hydroxylamine from hydroxylammonium sulfate over Pd/alumina - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2008)
Influence of the concentration of bromide (KBr) promoter, reaction period, temperature, catalyst loading and initial concentration of hydroxylammonium sulfate on the formation of H2O2 due to the reaction between hydroxylamine from the hydroxylammonium salt and molecular oxygen over Pd (1 wt%)/Al2O3 catalyst in a neutral aqueous medium at close to the ambient conditions has been investigated. Effect of pH and temperature on the destruction of H2O2, Occurring in the consecutive reactions, over the catalyst in the presence or absence of bromide promoter and hydroxylamine has also been studied. In the absence of O-2, the conversion of hydroxylamine by its decomposition over the catalyst increases sharply with increasing the pH, particularly above the pH of 7.0; at or below the pH of 7.0, it is quite small. The H2O2 destruction increases markedly with increasing the pH of medium and reaction temperature but it is found to decrease in the presence of hydroxylamine. For the highest net H2O2 formation, not only the optimum pH (7.0) of reaction medium but also the optimum other reaction conditions (viz. bromide promoter concentration, reaction period, temperature or catalyst loading) are necessary. The reaction path and mechanism for the generation of H2O2 have also been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: H2O2 destruction; Hydrogen peroxide; hydroxylamine; Hydroxylammonium sulfate; Pd/Al2O3 catalyst; reduction of O-2